Fostering Students’ Reading Comprehension through Dynamic Assessment - Rahayu, Widiyanti; Prastikawati, Entika Fani; Wiyaka, Wiyaka; Lestari, Maria Yosephin Widarti (Language Circle: Journal of Language and Literature, 2022)
This study emphasizes the implementation of dynamic assessment in reading comprehension in the English classroom of the tenth grade in senior high school. To reach this goal a mixed method as a design was used by the writers by applying a quasi-experimental research design and followed by a qualitative research design. There were two groups; the experimental class and the control class. The total amount of students who participated in this study was sixty students. In collecting the data, the writers used a reading comprehension test and an open questionnaire. After the data was collected the writers analyze the quantitative data using SPSS 21 such as; mean score and N-Gain. Meanwhile, the thematic analysis was carried out to analyze the open questionnaire. The findings of the studies should that the students reading comprehension in the experimental class are at a better level rather than the students in the control class. Moreover, according to the N-Gain measurement, the students reading comprehension in the experimental class show higher improvement when exposed to dynamic assessment.